2016
DOI: 10.2174/1573399811666150515125349
|View full text |Cite
|
Sign up to set email alerts
|

Depression Associated with Diabetes: From Pathophysiology to Treatment

Abstract: Diabetes is a chronic and progressive syndrome commonly associated with several neuropsychiatric comorbities, of which depression is the most studied. The prevalence of depression is about two or three times higher in diabetic patients compared to the general population. It is believed that the diabetes - depression relation may be bidirectional, i.e., the depression can lead to diabetes and conversely diabetes could facilitate the emergence of depression. Depression is one of the most neglected symptoms in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 0 publications
0
23
0
8
Order By: Relevance
“…Ainda no que diz respeito aos sintomas depressivos, apresentaram maior prevalência os pacientes que relataram mudança da alimentação após o diagnóstico de DM. Estudos indicam que os sintomas depressivos podem influenciar negativamente na adesão ao tratamento da doença e no controle glicêmico, o que pode ser explicado por sentimentos de ansiedade, medo e dificuldade de aceitação da doença em pacientes que possuem uma doença crônica, principalmente nas fases iniciais onde o paciente terá que se adaptar a mudanças na alimentação e demais práticas de estilo de vida, além de questões fisiológicas e de interação medicamentosa [10,11,17]. Da mesma forma, esse dado sugere que a necessidade de restrição alimentar devido à doença pode desencadear sentimentos de negação e frustração nessa população.…”
Section: Discussionunclassified
“…Ainda no que diz respeito aos sintomas depressivos, apresentaram maior prevalência os pacientes que relataram mudança da alimentação após o diagnóstico de DM. Estudos indicam que os sintomas depressivos podem influenciar negativamente na adesão ao tratamento da doença e no controle glicêmico, o que pode ser explicado por sentimentos de ansiedade, medo e dificuldade de aceitação da doença em pacientes que possuem uma doença crônica, principalmente nas fases iniciais onde o paciente terá que se adaptar a mudanças na alimentação e demais práticas de estilo de vida, além de questões fisiológicas e de interação medicamentosa [10,11,17]. Da mesma forma, esse dado sugere que a necessidade de restrição alimentar devido à doença pode desencadear sentimentos de negação e frustração nessa população.…”
Section: Discussionunclassified
“…These receptor proteins are induced by BDNF and are essential for protection of the retinal cells. This difference along with epigenetic modification, genetic variations bring to the platform that somewhere BDNF could also be concerned in hypoglycemic agent (insulin) resistance and within the pathological process of T2DR, altering TrKB receptor [37] . A study in animal model demonstrated that during initial stage of T2DR, necrobiosis of retinal ganglion cells (RGCs) occur and at the same time lack of BDNF is associated with retinal neuro-degeneration.…”
Section: Bdnf Vs Type 2 Diabetic Retinopathymentioning
confidence: 99%
“…The prevalence of depression among patients with diabetes is two to three times higher than in the general population ( 42 ). The diabetes—depression relation is usually bidirectional, with diabetes increasing the likelihood of depression and depression contributing to type 2 diabetes, usually through the presence of a lifestyle leading to obesity as well as through other mechanisms ( 42 ).…”
Section: The a To Z List For Managing Type 2 Diabetes In Culturally Dmentioning
confidence: 99%
“…The prevalence of depression among patients with diabetes is two to three times higher than in the general population ( 42 ). The diabetes—depression relation is usually bidirectional, with diabetes increasing the likelihood of depression and depression contributing to type 2 diabetes, usually through the presence of a lifestyle leading to obesity as well as through other mechanisms ( 42 ). It is believed that dysregulation of the hypothalamic pituitary-adrenal axis and of neurotransmitter systems, especially the monoaminergic system, oxidative stress and neuroinflammation may influence this relationship ( 42 ).…”
Section: The a To Z List For Managing Type 2 Diabetes In Culturally Dmentioning
confidence: 99%